Ion-acoustic wave activity in m = 0 helicon plasmas - Shamrai, K.P.; Virko, V.F.; Slobodyan, V.M.; Virko, Yu.V.; Kirichenko, G.S. (Вопросы атомной науки и техники, 2006)
The results of experimental and theoretical study of low-frequency (LF) wave activity in a helicon plasma and in an inductively coupled magnetized plasma are presented. This activity is shown to relate to ion-acoustic (IA) waves whose spectra can be either noise and continuous, or spiky, or combined. The origin of activity is ascertained from correlative measurements of wave characteristics, stationary plasma parameters, and plasma diamagnetic response. Various driving mechanisms of the IA waves are discussed.